The perceived impact of interprofessional information sharing on young people about their sexual healthcare. Issue 4 (3rd July 2016) - Hyde, Abbey; Fullerton, Deirdre; Lohan, Maria; McKeown, Caroline; Dunne, Laura; Macdonald, Geraldine; Howlin, Frances; Healy, Maria
ABSTRACT: This article presents the results from an analysis of data from service providers and young adults who were formerly in state care about how information about the sexual health of young people in state care is managed. In particular, the analysis focuses on the perceived impact of information sharing between professionals on young people. Twenty-two service providers from a range of professions including social work, nursing and psychology, and 19 young people aged 18–22 years who were formerly in state care participated in the study. A qualitative approach was employed in which participants were interviewed in depth and data were analysed using modified analytical induction (Bogdan & Biklen, 2007). Findings suggest that within the care system in which service provider participants worked it was standard practice that sensitive information about a young person's sexual health would be shared across team members, even where there appeared to be no child protection issues. However, the accounts of the young people indicated that they experienced the sharing of information in this way as an invasion of their privacy. An unintended outcome of a high level of information sharing within teams is that the privacy of the young person in care is compromised in a way that is not likely to arise in the case of young people who are not in care. This may deter young people from availing themselves of the sexual health services.